A mixed methods protocol to evaluate the effect and cost-effectiveness of an Integrated electronic Diagnosis Approach (IeDA) for the management of childhood illnesses at primary health facilities in Burkina Faso. (December 2015) - Blanchet, Karl; Lewis, James; Pozo-Martin, Francisco; Satouro, Arsene; Somda, Serge; Ilboudo, Patrick; Sarrassat, Sophie; Cousens, Simon
Abstract Background Burkina Faso introduced the Integrated Management of Childhood Illnesses (IMCI) strategy in 2003. However, an evaluation conducted in 2013 found that only 28 % of children were assessed for three danger signs as recommended by IMCI, and only 15 % of children were correctly classified. About 30 % of children were correctly prescribed with an antibiotic for suspected pneumonia or oral rehydration salts (ORS) for diarrhoea, and 40 % were correctly referred. Recent advances in information and communication technologies (ICT) and use of electronic clinical protocols hold the potential to transform healthcare delivery in low-income countries. However, no evidence is available on the effect of ICT on adherence to IMCI. This paper describes the research protocol of a mixed methods study that aims to measure the effect of the Integrated electronic Diagnosis Approach innovation (an electronic IMCI protocol provided to nurses) in two regions of Burkina Faso. Methods/design The study combines a stepped-wedge trial, a realistic evaluation and an economic study in order to capture the effect of the innovation after its introduction on the level of adherence, cost and acceptability. Discussion The main challenge is to interconnect the three substudies. In integrating outcome, process and cost data, we focus on three key questions: (i) How does the effectiveness and the cost of the intervention vary by type of health worker and type of health centre? (ii) What is the impact of changes in the content, coverage and quality of the IeDA intervention on adherence and cost-effectiveness? (iii) What mechanisms of change (including costs) might explain the relationship between the IeDA intervention and adherence? Trial registration Clinicaltrials.gov, NCT02341469 .